Diurnal and Seasonal variability of Ozone with its Precursors Gases at Jabalpur (International Journal of Scientific Research and Management (IJSRM), 2015)
Ozone is an allotrope generally found in the upper atmosphere in between the layer of troposphere and stratosphere; a layer ozonosphere. In the lower atmosphere, ozone has some precursor gases like CO, NO2, CH4 and TNMHC. These precursor gases fluctuates the concentration of O3 diurnally as well as seasonally. Through the study in Jabalpur (2013 and 2014), the diurnal and seasonal variation of O3 and its precursor gases had been observed. CO, CH4 and NO2 concentration was slightly upward in the year 2014 than 2013; whereas, concentration of O3 and TNMHC was throughout high in the year 2013. The concentration of O3 goes upwards the maximum with higher concentration of CO and NO2, with a combination of moderate TNMHC and declined CH4 concentration. The seasonal trend of 2013 was lower than 2014. The O3 and NO2 concentration increased during winter season whereas CO increased in summer.